Utilization of AI Media in Christian Religious Education: Effectiveness, Challenges, and Impact - Mujiono, Ponco; Wibowo, Daniel Ari (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The advancement of artificial intelligence (AI) technology has brought significant changes across various fields, including Christian religious education. However, its implementation still faces multiple challenges related to effectiveness, acceptance, and its impact on teaching and learning. This study aims to analyze the effectiveness of AI-based media in Christian education, identify the challenges that arise in its application, and explore its impact on both students and educators. This research employs a qualitative approach using a literature review method. Data were collected through an analysis of relevant literature sources, including academic journals, books, and research reports discussing the use of AI in Christian religious education. Thematic analysis was used to identify key patterns in the utilization of AI in this context. The findings reveal that AI-based media can enhance student engagement, provide more interactive learning materials, and support personalized learning experiences. However, several challenges remain, such as the limitations of AI in understanding theological concepts, concerns about the potential reduction of spiritual values in technology-based learning, as well as technical barriers and educators' readiness to adopt AI. In conclusion, the integration of AI in Christian religious education offers significant opportunities to improve learning effectiveness, but it requires a thoughtful approach to ensure alignment with theological and pedagogical principles. The implications of this study emphasize the need for curriculum development that ethically integrates AI, as well as the enhancement of digital literacy among educators and students.